You are Kind, you are Smart, you are Important: the Linkages between Individual Factors and the Intention to Repatriate among Malaysian Self-Initiated Expatriates - Siti Fatimah; Lilis Surienty . (Journal of Social and Development Sciences, 2013)
‘Brain drain’ is a terminology used to describe the migration of people endowed with a high level of human capital. Countries, a developing such as Malaysia, consider this to be a detrimental effect to the country’s growth with the outflow movement of their talented professionals. Problems seem to increase when these individual have silo mentalities regarding their home countries’ development when they show limited number of return. Thus, there is a need to study the determinants of the intention to repatriate among these talented professionals. In addition, it becomes a more interesting study when it is directed to the selfinitiated expatriates who determine their own outgoing and incoming. The development of the proposed model would be in line with the Malaysian government efforts to attract the talented professionals to serve their home country. The theoretical framework for this study consists of factors from the individual perspective and their relationships with the intention to repatriate. The Theory of Reasoned Action developed by Fishbein seems to be the appropriate theory to be applied in this study explaining factors to determine intention. This paper concentrates more on conceptualizing the relationship between individual’s factors and the intention to repatriate among the self-initiated expatriates. Based on a review of extent literature on self-initiated expatriates and the intention to repatriate, a model is presented and propositions outlined for future empirical testing.